How do public libraries respond to patron queries about opioid use disorder? A secret shopper study. Issue 4 (October 2021) - Wong, Vivien; Cannuscio, Carolyn C.; Lowenstein, Margaret; Feuerstein-Simon, Rachel; Graves, Rachel; Meisel, Zachary F.
Background: Improving linkage to opioid use disorder (OUD) treatment and services is a public health priority. Public libraries, a community resource for health information, may be well positioned to support and guide people who use drugs, as well as their families and friends. In this study, we sought to evaluate the availability and types of resources offered to patrons inquiring about OUD information, OUD treatment, and naloxone access. Methods: We conducted an audit (secret shopper) study from April 2019 to June 2019 in which an auditor anonymously called Pennsylvania public libraries. We used a purposive sampling strategy to select libraries located in geographically diverse regions across the urban-rural continuum. We categorized responses and verified via phone or website whether referrals to treatment centers and other organizations provided OUD treatment or services. Results: We obtained responses from 100 public libraries located across 48 of the 67 counties in Pennsylvania. Among the libraries that responded, 57 provided health information resources (e.g., books, websites) and 82 provided "next step" referrals to an organization that could provide further assistance. Among the libraries that provided referrals, 39 were to treatment centers, of which 33 were specifically to treatment centers that offer medications for OUD. Of the responding libraries, 28 communicated information about naloxone access. Conclusion: Public libraries can and do connect patrons to OUD treatment and support services; however, there is wide interlibrary variation in the resources presented, demonstrating opportunities for improvement in how libraries engage and refer patrons with substance use needs.